(untitled) (مجلة إحالات, 2025)
تمثل الدلالة حجر الزاوية في بنية اللغة الإنسانية؛ لأنها تُعادل القيمة النفعية للغة على مستوييها الإبلاغي والجمالي، وقد كان الفلاسفة المسلمون على وعيٍ كامل بهذه القيمة الاستثنائية لعنصر الدلالة في بنية اللغة، ولكن الأقلام والأنامل كانت تتجه صوب اللغويين في كل مرة يُذكر فيها البحث الدلالي. ونحن من خلال هذه المقالة سنحاول أولا أن نبيّن أنّ موضوع علم الدلالة ليس حكرا على اللغويين دون الفلاسفة المسلمين؛ إذ أنّ قضية الدلالة وعلاقتها بالمعنى من ضِمنَ اهتمامات الفلاسفة إذ تناولوها لصلتها الوثيقة بالألفاظ والتفكير هذا من جهة، ومن جهة أخرى سنورد ملامح التفكير الدلالي الصوتي عند الفلاسفة المسلمين من خلال أقسام الدلالة الصّوتية مبرزين معالم التميز والخصوصية في معالجة كل ما له علاقة بهذه الأخيرة. Significance represents the cornerstone of the structure of the human language, because it is equivalent to the utilitarian value of language at both the informative and aesthetic levels, and Muslim philosophers were fully aware of this exceptional value of the significance element in the structure of the language, but pens and fingers were moving towards linguists every time the semantic research was mentioned. Through this article, we will first try to show that the subject of semantics is not exclusive to linguists without Muslim philosophers, as the issue of semantics and its relationship to meaning is among the interests of philosophers, as they dealt with it in relation to the close relevance of words and thinking on the one hand, and on the other hand we will mention the features of semantic vocal thinking when Muslim philosophers highlight the features of excellence and privacy in dealing with everything related to phonemic significance.